Ὡς ὁ βασιλεὺς ἄγει. Some considerations on the double dating formulas of Greek inscriptions from Parthian Babylon (Atti del Sodalizio Glottologico Milanese, 2024)
This paper examines two Greek inscriptions written in Babylon during the Parthian period with specific focus on the sections containing double dating formulas. Unfortunately, both inscriptions – particularly the first – are damaged. This paper shows that strong evidence in favor of one of the text reconstructions proposed by scholars can be obtained by means of an analysis combiningthe methods and tools of philology and historical (socio)linguistics. Evidence from other languages is also considered.